UV-band and acid rain effects on beach ( Fagus sylvatica L.) and holm oak ( Quercus ilex L.) leaves - Paoletti, E (Chemosphere, 1998)
Beech (Fagus sylvatica L.) and holm oak (Quercus ilex L) leaves were subjected to simulated acid rain and UV-B radiation for 10 days. The almost glabrous beech leaves revealed a greater predisposition to developing macroscopic necrotic lesions than the pubescent holm oak leaves. This response is due primarily to their different morpho-anatomical structure, rather than to a difference in the synthesis of UV-B absorbing pigments (flavonoids); the response was also accompanied by microscopically observable alterations (collapse of epidermal cells, fusion of surface wax structures, structural damage to the stomata) and by the reduction of stomatal conductance
Keywords: acid rain; beech; damage; Holm oak; leaves; necrosis; stomatal conductance (voyant); uv-b radiation

Trichome density and its UV-B protective potential are affected by shading and leaf position on the canopy - Liakoura, V; Stefanou, M; Manetas, Y (Environmental and Experimental Botany, 1997)
In Olea europaea trichome density and UV-B absorbing compounds of leaf hairs and the lamina proper of leaves located in south-facing, north-facing and the internal of the canopy were positively correlated to the UV-B midday instant irradiance measured in September at these three different positions of the canopy. The correlation between these three parameters and the receiving photosynthetically active radiation (PAR), however, was weaker. In Quercus ilex, trichome density and its UV-B absorbing capacity were considerably higher in the exposed, south-facing leaves, compared to the deeply shaded ones; the UV-B absorbing capacity of the de-haired lamina, however, was the same. In the broad- leaved, alpine rosette of Verbascum speciosum, one could distinguish two areas on the leaves, one exposed and one shaded by the superimposed lamina. Although trichome density and the UV-B absorbing compounds of the de-haired leaf were the same in the two areas, the UV-B absorbing capacity of hairs was considerably increased in the exposed region. In V. speciosum, exposure induced also qualitative changes in the UV-B absorbance profile, apparently due to the formation of new flavonoid compounds absorbing maximally at 345-350 nm. In all other cases, the differences were mainly quantitative. The results support the postulate of a function of leaf hairs as a UV-B radiation screen and suggest that trichome density and/or its UV-B absorbing capacity may depend on irradiance during leaf development.
Keywords: leaf hairs; Olea europaea; phenolics; Quercus coccifera; Quercus ilex; uv-b radiation; verbascum speciosum

Trichome density and its UV-B protective potential are affected by shading and leaf position on the canopy - Liakoura, V.; Stefanou, M.; Manetas, Y. (Environmental and Experimental Botany, 1997)
In Olea europaea trichome density and UV-B absorbing compounds of leaf hairs and the lamina proper of leaves located in south-facing, north-facing and the internal of the canopy were positively correlated to the UV-B midday instant irradiance measured in September at these three different positions of the canopy. The correlation between these three parameters and the receiving photosynthetically active radiation (PAR), however, was weaker. In Quercus ilex, trichome density and its UV-B absorbing capacity were considerably higher in the exposed, south-facing leaves, compared to the deeply shaded ones; the UV-B absorbing capacity of the de-haired lamina, however, was the same. In the broad- leaved, alpine rosette of Verbascum speciosum, one could distinguish two areas on the leaves, one exposed and one shaded by the superimposed lamina. Although trichome density and the UV-B absorbing compounds of the de-haired leaf were the same in the two areas, the UV-B absorbing capacity of hairs was considerably increased in the exposed region. In V. speciosum, exposure induced also qualitative changes in the UV-B absorbance profile, apparently due to the formation of new flavonoid compounds absorbing maximally at 345-350 nm. In all other cases, the differences were mainly quantitative. The results support the postulate of a function of leaf hairs as a UV-B radiation screen and suggest that trichome density and/or its UV-B absorbing capacity may depend on irradiance during leaf development.
Keywords: leaf hairs; Olea europaea; phenolics; Quercus coccifera; Quercus ilex; uv-b radiation; verbascum speciosum